ANALISA PERFORMA KERJA STERILIZER OF CRUDE PALM OIL - Bismantolo, Putra; Abdul Latif Mubarok; A. Sofwan (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2022)
Boiling is one of the main factors that determine the success of the palm oil production process. Palm oil processing mills obtain Crude Palm Oil (CPO) through a boiling process at the sterilizer station to separate loose fruit and empty fruit, which will then be pressed into CPO. Boiling at the sterilizer station used is saturated steam with a pressure of 1.5-3 bar which is injected from the back pressure vessel (BPV). The selected boiling system is always adjusted to the ability to provide steam at the boiler station that produces steam. In this case, the supply of steam is considered sufficient, so that the boiling system used is the Triple Peak system, and the boiling time is ± 90 minutes.